A SYBR green I-based multiplex real-time PCR for simultaneous detection of pseudorabies virus, porcine circovirus 3 and porcine parvovirus - Lihua Cao; Wenke Lv; Anqi Li; Lulu Yang; Feng Zhou; Feng Wen; Sheng Yuan; Shujian Huang; Zhili Li; Jinyue Guo (BMC Veterinary Research)
Abstract Background Pseudorabies virus (PRV), porcine parvovirus (PPV) and porcine circovirus 3 (PCV3) are common in swine farms in China. Single infection or co-infection with PRV, PPV and/or PCV3 was difficult to distinguish between their clinical symptoms and pathological changes. Therefore, a quick and accurate detection method is needed for epidemiological surveillance, disease management, import and export control. Methods In the present study, we established a multiplex real-time PCR assay based on SYBR Green I for the simultaneous detection of PRV, PPV and PCV3 genomes. Results PRV, PPV and PCV3 were distinguished in the same sample by their different melting temperatures (Tm), with melting peaks at 90 °C for PRV, 84 °C for PPV and 80 °C for PCV3, respectively, and other non-targeted swine pathogens did not exhibit specific melting peaks. The assay showed a high degree of linearity (R2≧0.995), and the detection limits were 4.76 copies/μL for PRV, 3.67 copies/μL for PPV, 3.07 copies/μL for PCV3 and 1.87 × 102 copies/μL for the three mixed plasmids, respectively. In this research, 81 clinical samples from pig farms in nine different regions of Guangdong Province were used to evaluate this new method. The detection rate of the multiplex real-time PCR assay was higher than that of the conventional PCR assay. Conclusions This multiplex real-time PCR assay could be used as a diagnostic tool that is rapid, sensitive and reliable for the detection of co-infection of PRV, PPV and PCV3 as well as for molecular epidemiological surveillance.